2010
DOI: 10.5001/omj.2010.56
|View full text |Cite
|
Sign up to set email alerts
|

In Vitro Susceptibility Test of Different Clinical Isolates against Ceftriaxone

Abstract: Ceftriaxone can be used as a drug of choice in infections caused by S. aureus, E. coli, P. aurigenosa, K. pneumonia and S. typhi. However, it should be used with other antimicrobial agents in order to increase its effectiveness against P. mirabilis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
9
0
2

Year Published

2011
2011
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 18 publications
(18 reference statements)
2
9
0
2
Order By: Relevance
“…Among all brands, B6 showed higher activity against E. coli , S. aureus and Pseudomonas aueresinosa ; B1 showed higher activity against S. typhi . The study conducted in Pakistan by Masood and Aslam showed clinical isolates were resistant to ceftriaxone [8]. Similarly, the study conducted at Nepal with three ceftriaxone brands showed only six isolates were resistant against Brand C tested, but the other A and B were susceptible against all isolates [9].…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…Among all brands, B6 showed higher activity against E. coli , S. aureus and Pseudomonas aueresinosa ; B1 showed higher activity against S. typhi . The study conducted in Pakistan by Masood and Aslam showed clinical isolates were resistant to ceftriaxone [8]. Similarly, the study conducted at Nepal with three ceftriaxone brands showed only six isolates were resistant against Brand C tested, but the other A and B were susceptible against all isolates [9].…”
Section: Discussionmentioning
confidence: 94%
“…resistant to ceftriaxone. [8] Similarly, the study conducted at Nepal with three ceftriaxone brands showed only six isolates were resistant against Brand C tested, but the other A and B were susceptible against all isolates. [9] Humza studied the in-vitro comparative efficacy of various antibiotics against P. aeruginosa; results reveal that ceftriaxone has no sensitivity.…”
Section: Discussionmentioning
confidence: 95%
“…The antibiotic policy guidelines preparation is the need to avoid any bitter experience of misuse of this class of drug therapy, the team efforts of the members comprising consultants, prescribing physicians, and members of health services team should participate in producing an effective plan to make better decisions in this regards (Masood, 2010). In addition, surveillance programs should be conducted periodically to evaluate the sensitivity and susceptibility of these bacteria against prescribed antibiotics.…”
Section: P Aeruginosa Isolated From Various Clinical Samplesmentioning
confidence: 99%
“…Since the emergence of resistance remains silent for some periods and takes time to become apparent, these antibiotics should be prescribed with cautions so that the bitter experience of antibiotic resistance can be avoided (Jombo et al, 2010). These in vitro sensitivity studies also help in cost-effective; prescribing different brands of the antibiotic to the different patients with varying socioeconomic back-grounds (Masood, 2010). Overall, resistance patterns in different regions should be conducted so that the profiles of the specific region are maintained and monitored accordingly.…”
Section: P Aeruginosa Isolated From Various Clinical Samplesmentioning
confidence: 99%
“…This study will help physicians, clinicians and consultants to decide its use in the most appropriate clinical infections. Microbial drug resistance is an unavoidable outcome of the use of antimicrobial agents [6]. The present study identified the various non-fermenters by staining techniques.…”
Section: Introductionmentioning
confidence: 99%